Pengaruh E-Marketing Mix terhadap Brand Loyalty - Astuti, Ayu Widiya; Aulia, Azzira Sabrina; Salsabila, Nadhifah Shofy (Program Studi Akuntansi IKOPIN, 2022)
The use of the internet and technology is currently growing rapidly and penetrated in various fields. Many companies are using it to increase productivity and company life span. One of the fields that use it is marketing or often referred to as E-Marketing. The role of E-Marketing itself is currently very important because it will increase the productivity of companies that use it and increase consumer loyalty because of the satisfaction it gets. Several previous researchers have conducted research to determine the effect of E-Marketing on Brand Loyalty. This research was conducted with the aim of knowing the effect of several variables in the E-Marketing Mix, namely Price Intelligence, Delivery Risk, Promotion Intelligence and The E-Product on Brand Loyalty. Samples were taken from 100 respondents using purposive sampling. The data analysis method used in this research is Multiple Linear Regression with the help of SPSS to process the data. The results show that there is a strong relationship between the variables of E-Marketing and Brand Loyalty, Price Intelligence has no effect on Brand Loyalty, Delivery Risk has no effect on Brand Loyalty, Promotion Intelligence has no effect on Brand Loyalty and E-product has no effect on Brand Loyalty. Further research is expected to be able to use different variables between E Marketing Mix and Brand Loyalty and research is carried out in more depth on an ongoing basis.